Desenvolvimento de um implante de coluna cervical biorreabsorvível - Souza, Fernando Lourenço de (2015)
The interaction between health areas with engineering are assisting in development of techniques and devices that provide a better quality of life for society. One of the most striking results in modern society is the use of biomaterials to manufacture implants. In this sense, polymeric materials have gained significant importance in surgical treatments, especially bioresorbable polymers, because once in contact with the body fluids, the degradation process starts, so that they disappear completely from the body within a certain time. In surgical procedures, implants produced with these materials must withstand the loads imposed by osteosynthesis process, especially in complex biological structures such as the spine. In this case, the surgical procedure for arthrodesis of spine, usually, uses titanium implants that require specific fixation procedures, which lengthen the surgical procedure, in general increasing the costs. Therefore, the objective of this work was to design a new implant for cervical spine made of bioresorbable material. The validation of this new implant was performed using finite element modeling compared to an imported implant system used in spinal arthrodesis. The new implant is made by a structure such as a honeycomb, which receives the bone graft and four inclined screws within vertebrae working area. The implant bearing plate has holes with threads to assist screw fixing. It was found that the new implant is dimensioned for loads imposed on the column and provides good structural stability. It was observed that while the bone graft was not bound, the displacements are practically restricted by implant structure. However, with the implant material degradation, the fixation of the vertebrae is transferred to the bone structure, formed by the graft in approximately 9 months.